2015
DOI: 10.1016/j.gr.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable insights into the paleoecology of the Avalonian Ediacaran macrobiota

Abstract: Ediacaran macrofossils from the Avalon Terrane (primarily eastern Newfoundland and the central U.K.) record some of the earliest large and complex multicellular organisms on Earth.Perhaps the greatest unknown regarding these fossils is their relevance to the early evolutionary history of the Kingdom Animalia. In recent years, new data and discoveries have revealed insights into Ediacaran paleobiology, taxonomic relationships, paleoecology and taphonomy, significantly refining our understanding of Avalonian eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 242 publications
(164 reference statements)
3
139
0
Order By: Relevance
“…Clapham et al 2003), but this has been shown to be inaccurate (Antcliffe & Brasier 2007); more recent computational models support passive suspension feeding in the enigmatic Tribrachidium (Rahman et al 2015). However, clear evidence for the presence of pores allowing the uptake of particulate matter is currently lacking (Liu et al 2015). Alternatively, DOM could be absorbed through cell surfaces, as has been proposed for Ediacaran forms with large surface areas such as rangeomorphs ).…”
Section: Feeding Strategies Of Ediacaran Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clapham et al 2003), but this has been shown to be inaccurate (Antcliffe & Brasier 2007); more recent computational models support passive suspension feeding in the enigmatic Tribrachidium (Rahman et al 2015). However, clear evidence for the presence of pores allowing the uptake of particulate matter is currently lacking (Liu et al 2015). Alternatively, DOM could be absorbed through cell surfaces, as has been proposed for Ediacaran forms with large surface areas such as rangeomorphs ).…”
Section: Feeding Strategies Of Ediacaran Organismsmentioning
confidence: 99%
“…The biological affinity of Ediacaran organisms remains enigmatic, but recent work tends to characterize them as stem-or crown-group metazoans (see Liu et al 2014Liu et al , 2015, potentially representing multiple clades that have been preserved under a common taphonomic regime ). Molecular clock data suggest that the origin of metazoans predates the late Ediacaran period, with many major clades radiating during the Cryogenian and early Ediacaran (dos Reis et al 2015;Erwin 2015).…”
mentioning
confidence: 99%
“…Similar observations have been made in the Ravens Throat River Lagerstätte, where coprolites preserve spreiten structures (unpublished observation). It is unlikely that the structures represent poorly preserved jellyfish, eldonids, or Ediacaran-like discoidal fossils, as no rays, ridges, or circular structures are preserved; typical features of such fossils (Liu et al 2015, Lieberman et al 2017, McMahon et al 2017, Sappenfield et al 2017.…”
Section: Coprolite Origin and Producersmentioning
confidence: 99%
“…Menon et al (2013Menon et al ( , 2014 controversially argued that A. terranovica fossils may suggest evidence of vertical and horizontal movement consistent with the behaviour of cnidarians, however Retallack (2014) disputed this argument. Liu et al (2015) argued the possibility "that Aspidella reflects several very different original entities, including holdfast discs, microbial colonies (cf. Grazhdankin and Gerdes, 2007), and discrete organisms (cf.…”
Section: The Reverend Moses Harvey and His 1868 Discovery Of Fossilsmentioning
confidence: 99%
“…3) fossil Oldhamia flabellata (Hofmann et al 2008;Liu et al 2015). However, there is no evidence that Harvey's presumed Oldhamia fossils could have been referable to P. bonavistensis.…”
Section: Other Studies Of the Fossils At Issuementioning
confidence: 99%